Caring behaviors of preceptors as perceived by new nursing graduate orientees - Schumacher, Donna Lucas, author; Davies, Timothy Gray, advisor; Banning, James H., committee member; Hall, Bruce, committee member; Forsyth, Diane, committee member (Colorado State University. Libraries, 2005)
Caring has been purported to be the core essence in nursing however, a review of the literature yields no studies examining if caring behaviors and interactions occur between new nursing orientees and their preceptors. This phenomenological study explored the orientee and preceptor relationship and asked the questions; do caring interactions occur between preceptors and orientees and if so, what does this mean to the orientee. A purposeful sample of 10 new graduate nursing orientees attending a 10-week orientation period at a large medical center in the Midwestern part of the United States, participated in this study by journaling their thoughts, and feelings about preceptor caring and not so caring interactions that occurred. Journal entries were coded for themes and sub themes. Participant's journals demonstrating specific and rich examples about caring and not so caring behaviors from their preceptors were asked to partake in an in-depth interview. Interviews were analyzed using the Colaizzi methodology. Comparisons of the journal themes and sub themes were compared with the themes extracted from the interviews. Caring and not so caring preceptor behaviors and the powerful meanings and outcomes for the orientees were expressed. Trustworthiness was maintained using reflexive bracketing, peer review and member checking. Six themes of caring preceptor behaviors emerged; advocating, welcoming, including, autonomy with appropriate preceptor presence, making human connections, and authentic, specific, and non-punitive feedback. Four themes of not so caring preceptor behaviors also emerged, were antithesis to the caring preceptor behaviors, and included; unwelcoming, autonomy with over or under preceptor presence, unclear, nongenuine feedback. None of the orientees felt comfortable discussing their concerns and feelings with uncaring preceptors. This was due in part to their strong desire to fit into the nursing culture of the unit. This study provides actual preceptor caring and not so caring behaviors and demonstrates the resultant powerful outcomes. This study can be used in preceptor education to increase the awareness of caring interactions. Caring interactions help new orientees to become independent, safe and accountable nurses, and these positive outcomes can increase retention of nurses at a time when the nursing shortage is critical.
Keywords: nursing; health education